Garden City Sanitarium - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of large buildings with a driveway lined in palm trees. The smaller building to the right is covered in ivy and a car is parked beneath the trees in the driveway to the left.